Secondhand smoke and respiratory ill health in current smokers. Issue 5 (23rd September 2005) - Lam, T-H; Ho, L-M; Hedley, A J; Adab, P; Fielding, R; McGhee, S M; Leung, G M; Aharonson-Daniel, L
Abstract : Background: Numerous studies have concluded that secondhand smoke (SHS) is harmful to non-smokers but controversy persists regarding its effects on smokers. The impact of SHS exposure on the acute respiratory health of current active smokers was examined using a cross sectional design. Methods: 9923 uniformed staff in the Hong Kong Police Force completed a standardised questionnaire on current and past smoking, SHS exposure at home and at work, acute respiratory symptoms, and recent physician consultation. 3999 male current smokers were included in the analysis. Results: About 5% of the smokers were exposed to SHS at home only, 53% were exposed at work only, and 30% were exposed both at home and at work. The prevalence ratios for respiratory symptoms (throat and nasal problems, cough, phlegm, and wheeze), physician consultation, and self medication were higher for those who were exposed to SHS at home or at work. The odds ratios of reporting one or more respiratory symptoms, for SHS exposures at home or at work, were 1.33 (95% confidence interval (CI) 1.12 to 1.59) and 1.66 (95% CI 1.36 to 2.02) respectively, after adjusting for age, marital status, education, rank and duties, exposure to self perceived dusty or polluted environment in previous job, and total dose of active smoking. The adjusted odds ratios showed significant positive dose–response gradients with SHS exposure at home, at work, and at both places combined. Conclusions: SHS exposure is strongly associated with increased acute respiratory symptoms and recent outpatient service utilisation in current smokers. If the association is causal, public health action to limit SHS exposure could also benefit smokers.